Light regulation of coccolithophore host–virus interactions. Issue 3 (8th October 2018) - Thamatrakoln, Kimberlee; Talmy, David; Haramaty, Liti; Maniscalco, Christopher; Latham, Jason R.; Knowles, Ben; Natale, Frank; Coolen, Marco J. L.; Follows, Michael J.; Bidle, Kay D.
Summary: Viruses that infect photoautotrophs have a fundamental relationship with light, given the need for host resources. We investigated the role of light on Coccolithovirus (EhV) infection of the globally distributed coccolithophore, Emiliania huxleyi . Light was required for EhV adsorption, and viral production was highest when host cultures were maintained in continuous light or at irradiance levels of 150–300 μmol m −2 s −1 . During the early stages of infection, photosynthetic electron transport remained high, while RuBisCO expression decreased concomitant with an induction of the pentose phosphate pathway, the primary source of de novo nucleotides. A mathematical model developed and fitted to the laboratory data supported the hypothesis that EhV replication was controlled by a trade‐off between host nucleotide recycling and de novo synthesis, and that photoperiod and photon flux could toggle this switch. Laboratory results supported field observations that light was the most robust driver of EhV replication within E. huxleyi populations collected across a 2000 nautical mile transect in the North Atlantic. Collectively, these findings demonstrate that light can drive host–virus interactions through a mechanistic interplay between host metabolic processes, which serve to structure infection and phytoplankton mortality in the upper ocean.